CAI of Electromagnetics With Flicker-Free Time Varying Fields Powerfully Used to Enhance Learning - Hoole, S.R.H.; Aravinthan, S.; Kuganeswaran, T. (IEEE transactions on magnetics, 2009)
Computer-based depiction of electromagnetic fields is an important tool in the computer-aided instruction of the subject electromagnetics. It provides a means of physically imagining the abstract fields. Such time-varying pictures are being used but they require extensive graphics capabilities and advanced software operator ability to create. This paper shows how graphics frames that are the output of typical equipotential plots in rapidly and sequentially progressing time form a graphics data bank. These may be employed to flash them sequentially on the screen to picture time-varying fields. The double-buffering technique for avoiding flicker is presented. The Java-based system has been used as a means of powerful pedagogy to teach over the Internet depicting traveling waves, eddy currents, radiating fields and so on. Students can vary parameters and see the effects. The system has secondary use as a CAD system in designing where sensors are to be placed in measuring currents in a three-phase overhead line.